2018
DOI: 10.1371/journal.pone.0191279
|View full text |Cite
|
Sign up to set email alerts
|

Cadherins in the retinal pigment epithelium (RPE) revisited: P-cadherin is the highly dominant cadherin expressed in human and mouse RPE in vivo

Abstract: The retinal pigment epithelium (RPE) supports the health and function of retinal photoreceptors and is essential for normal vision. RPE cells are post-mitotic, terminally differentiated, and polarized epithelial cells. In pathological conditions, however, they lose their epithelial integrity, become dysfunctional, even dedifferentiate, and ultimately die. The integrity of epithelial cells is maintained, in part, by adherens junctions, which are composed of cadherin homodimers and p120-, β-, and α-catenins link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 65 publications
1
53
0
Order By: Relevance
“…We used mouse RPE as the native counterpart for hESC‐RPE in our studies due to unavailability of live human RPE tissue. Previous work on gene and protein expression profiles of human and mouse RPE show high similarity regarding general biological functions, canonical pathways, and molecular networks . However, there are important species‐specific differences between human and mouse RPE.…”
Section: Discussionmentioning
confidence: 99%
“…We used mouse RPE as the native counterpart for hESC‐RPE in our studies due to unavailability of live human RPE tissue. Previous work on gene and protein expression profiles of human and mouse RPE show high similarity regarding general biological functions, canonical pathways, and molecular networks . However, there are important species‐specific differences between human and mouse RPE.…”
Section: Discussionmentioning
confidence: 99%
“…In quiescent adult RPE cells, epithelial cadherins (E- and/or P-cadherin) sequester β-catenin at the AJs to maintain cell–cell contact. Reduction of cadherin levels or dissociation of AJs allows β-catenin to translocate into the nucleus, where it interacts with the transcription factor LEF, and activates the transcription of various genes, including Snail and cyclin D1, which participate in RPE cell EMT via the canonical Wnt/β-catenin signaling pathway ( Gonzalez & Medici, 2014 ; Lamouille, Xu & Derynck, 2014 ; Nelson & Nusse, 2004 ; Yang et al, 2018 ) . Tamiya, Liu & Kaplan (2010) suggested that the loss of P-cadherin causes the loss of cell–cell contact and initiates RPE cell migration and EMT.…”
Section: Survey Methodologymentioning
confidence: 99%
“…In quiescent adult RPE cells, epithelial cadherins (E-and/or P-cadherin) sequester β-catenin at the AJs to maintain cell-cell contact. Reduction of cadherin levels or dissociation of AJs allows β-catenin to translocate into the nucleus, where it interacts with the transcription factor LEF, and activates the transcription of various genes, including Snail and cyclin D1, which participate in RPE cell EMT via the canonical Wnt/β-catenin signaling pathway (Gonzalez & Medici 2014;Lamouille et al 2014;Nelson & Nusse 2004;Yang et al 2018) . Tamiya et al (2010) suggested that the loss of Pcadherin causes the loss of cell-cell contact and initiates RPE cell migration and EMT.…”
Section: The Polarized Retinal Pigment Epithelial Cellmentioning
confidence: 99%